Corporate Environmental, Social, and Governance Disclosure and Performance Dynamics : An Empirical Analysis of BRICS Nations - Dwibedi, Pruthiranjan; Pahi, Debasis; Mishra, Anjali Prava (Indian Journal of Finance, 2025)
Purpose : In this rapidly changing business scenario, environmental, social, and governance (ESG) factors are rapidly used by different stakeholders for decision-making. Investors are attracted to sustainable investing because of the growing adoption of ESG factors in investment decision-making. By elucidating the relationship between ESG disclosure score and firm profitability, this study tried to provide useful insights for investors, policymakers, and corporate barons seeking to enhance long-term financial resilience and societal impact through responsible business practices. Design/Methodology/Approach : This study consisted of 254 non-financial listed companies of Brazil, Russia, India, China, and South Africa (BRICS) nations over the period from 2011 to 2023. Data were collected from Thomson Reuters’ Refinitiv Eikon database to analyze the impact of ESG disclosure scores on financial performance and market performance of firms. This was analyzed by applying different GMM methods. Findings : The research revealed a positively significant impact of ESG disclosure score on financial performance (measured by return on assets and return on equity), whereas there was a negatively significant impact on market performance (measured by closing price and Tobin’s Q). Originality/Value : Empirical evidence on the nexus between ESG disclosure score and firm performance from an emerging nation context was limited. This research provided firsthand evidence in the area of sustainability performance from BRICS nations, as these five economies represented over 41% of the world’s population, 24% of global gross domestic product (GDP), and 16% of world trade and exhibited impressive economic growth potential.